Musicians as Workers and the Gig Economy - Cloonan Martin; Williamson John (TAYLOR & FRANCIS LTD, 2025)
Recent years have seen notions of the "gig economy" become widespread. Hitherto most analyses of this phenomenon have centered on first defining the phenomenon, then tracing its extent and effects before considering the policy implications. However, few previous accounts have concerned themselves with the origins of the word "gig," and none have focused on those workers whose lives revolve around gigs―musicians. This article seeks to address this lacuna and argues that a study of musicians' working lives has much to teach those interested in the development and implications of the gig economy, but also that the peculiarities of musical work so mean that such lessons have to be learned selectively.